Biocontrol of Botrytis cinerea on Grape Berries in Chile: Use of Registered Biofungicides and a New Chitosan-Based Fungicide - Mario Herrera-Défaz; Denis Fuentealba; Luciano Dibona-Villanueva; Daniel Schwantes; Belén Jiménez; Brenda Ipinza; Bernardo Latorre; Héctor Valdés-Gómez; Marc Fermaud (Horticulturae, 2023)
In organic phytosanitary management of vineyards, it is crucial to understand the available pathogen control alternatives in order to progress towards a more sustainable form of viticulture. The objective of this study was to evaluate the efficacy of seven biofungicides registered in Chile for the prevention and treatment of Botrytis Bunch Rot (BBR), and to test a novel fungicide composed of chitosan and riboflavin (CH-RF). Biofungicides including Trichoderma spp., Aureobasidium pullulans, and Melaleuca alternifolia were evaluated using biotests with grapevine berries. Registered products (specifically biological control agents) significantly reduced the in vitro growth of B. cinerea. However, the degree of pathogen control varied significantly among products in grapevine berries of the Chardonnay cultivar, and disease incidence and severity changed depending on the inoculation time. High control effectiveness was achieved with two biofungicides, A. pullulans (average efficacy 34%) and M. alternifolia oil (average efficacy 29%). In vitro tests showed CH-RF significantly reduced mycelial growth of B. cinerea. Noticeable differences between the new CH-RF fungicide (incidence under 50% and infection score under 1) and A. pullulans- and M. alternifolia-based products were detected in grapevine berries. Therefore, the new experimental formulation CH-RF constitutes a promising alternative for the control of B. cinerea and provides a basis for further research.